Soil, rhizosphere, and root microbiome in kiwifruit vine decline, an emerging multifactorial disease - Guaschino, Micol; Garello, Marco; Nari, Luca; Zhimo, Yeka V.; Droby, Samir; Spadaro, Davide (Frontiers in Microbiology, 2024)
Kiwifruit vine decline syndrome (KVDS) is characterized by severe root system impairment which leads to irreversible wilting of the canopy. Plants usually collapse rapidly from the appearance of the first above ground symptoms, without recovery even in the following seasons. The syndrome has been negatively impacting kiwifruit yield in different areas of Italy, the main producing European country, since its first outbreak in 2012. To date, a unique, common causal factor is yet to be found and the syndrome is referred to as multifactorial. In this paper, we investigated the whole biotic community (fungi, bacteria, and oomycetes) associated with the development of KVDS in three different belowground matrices/compartments (soil, rhizosphere, and root). Sampling was performed in both healthy and affected sites located in the main kiwifruit producing area of Northwestern Italy. To address the multifactorial nature of the syndrome and to investigate potential roles of abiotic factors in shaping these communities, physicochemical analysis of soils was also performed. This study investigates the associations among taxonomic groups composing the microbiome and also between biotic and abiotic factors. Dysbiosis was considered as a driving event shaping KVDS microbial communities. The results obtained from this study highlight the role of the oomycete genus Phytopythium, which resulted predominant in the oomycete community composition of diseased matrices, though it was also present in healthy ones. Both bacterial and fungal communities resulted in a high richness of genera, and majorly correlated to sampling site and matrix, underlining the importance of multiple location sampling both geographically and spatially. Rhizosphere community associated to KVDS resulted as driven by a dysbiotic process. In addition, analysis of association network in diseased rhizosphere, revealed the presence of potential cross- kingdom competition for plant-derived carbon between saprobes, oomycetes and bacteria.